Family as An Educational Environment That Can Provide Science Education for Children with Special Needs - Rina Maryanti; M. Asjjari (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study was to determine the science education provided by families to students with special needs. We used qualitative research methods. The subjects in this study were families and students with special needs (students with visual impairment, hearing impairment, intellectual disabilities, physical impairment, and Down syndrome) in one of the special schools in Indonesia. The results showed that most families fully gave up the responsibility for providing science education to school teachers. In addition, they thought that learning science is very complicated because it relates to formulas and numbers, so they thought children with special needs unable to learn about science. Whereas science education is very broad because it deals with natural phenomenon that occurs in everyday life. Students with special needs learned easily through the habituation process.